Persepsi Masyarakat Tentang Perbankan Syariah: Studi Kasus pada Desa Mbawa Kecematan Donggo Kabupaten Bima - Dede Gunawan; Ihwan p. Syamsudin; Jainuddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
the lack of public knowledge about Islamic banks so that many experience misperceptions in the sharia values that exist in these Islamic banks.... So this research aims to find out the Public Perception of Islamic Banking (Case Study in Mbawa Village, Donggo District, Bima Regency). This research will be conducted in Mbawa Village, Donggo District, Bima Regency, West Nusa Tenggara. This research uses Qualitative Research with a Case Study Approach. Data Collection Techniques are Observation, Interview and Documentation. Data Analysis Techniques are Data Reduction, Data Presentation and Conclusion Drawing. Based on the results of the study, it can be concluded that this research shows that the perception of the Mbawa Village community towards Islamic banking is still at the initial stage of understanding, where most people have a positive view of the existence of Islamic banks, although they do not fully understand the underlying principles. Basic concepts such as the prohibition of usury, the profit-sharing system, and contracts in financial transactions have not been fully understood in depth.